Effects of Medicare Part D Coverage Gap on Medication and Medical Treatment Among Elderly Beneficiaries with Depression - Zhang, Yuting (2012)
CONTEXT: Maintenance antidepressant pharmacotherapy in late life prevents recurrent episodes of major depression. Medicare Part D’s coverage gap (“gap”) could increase the likelihood of reducing appropriate medication treatment, thereby exposing older adults to increased risk for relapse of depressive episodes. OBJECTIVE: To determine whether: beneficiaries reduce antidepressant use in the gap; the reduction in antidepressants is similar to the reduction in cardiovascular and anti-diabetic medications; the provision of generic coverage reduces the risk of medication reduction; and medical spending increases in the gap. DESIGN: Observational study, pre-post-with-a-comparison-group design. SETTING AND PATIENTS: 5% random sample of US Medicare beneficiaries aged 65 and older with depression (n=65,223) enrolled in stand-alone Part D plans in 2007. MAIN OUTCOME MEASURES: Antidepressant pharmacotherapy, physician, outpatient and inpatient spending. RESULTS: Being in the gap was associated with comparable reductions in the use of antidepressant, cardiovascular and anti-diabetic medications. Relative to the comparison group (those who had full coverage in the gap due to Medicare coverage or low-income-subsidies), the no-coverage group reduced their monthly antidepressant prescriptions by 12.1% (95% CI 9.9%–14.3%) from the pre-gap level, while they reduced cardiovascular and anti-diabetic drug usage by 12.9% and 13.4% respectively. Those with generic drug coverage in the gap reduced their antidepressant monthly prescriptions by 6.9% (95% CI 4.8%–9.1%); this decrease was entirely attributable to the reduction in brand-name antidepressants. Medicare spending on medical care did not increase for either group, relative to the comparison group. CONCLUSIONS: The Medicare Part D’s coverage gap was associated with modest reductions in use of antidepressants. Those with generic coverage reduced only brand-name drugs and did not switch from brand-name to generic drugs. The reduction in antidepressant use was not associated with increase in non-drug medical spending.